2019
DOI: 10.1109/tcns.2018.2820499
|View full text |Cite
|
Sign up to set email alerts
|

Structured Decentralized Control of Positive Systems With Applications to Combination Drug Therapy and Leader Selection in Directed Networks

Abstract: We study a class of structured optimal control problems in which the main diagonal of the dynamic matrix is a linear function of the design variable. While such problems are in general challenging and nonconvex, for positive systems we prove convexity of the H2 and H∞ optimal control formulations which allow for arbitrary convex constraints and regularization of the control input. Moreover, we establish differentiability of the H∞ norm when the graph associated with the dynamical generator is weakly connected … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 60 publications
(113 reference statements)
0
12
0
Order By: Relevance
“…Under these assumptions, for all nonnegative initial condition x(0) and nonnegative input signal u(t) (t ≥ 0), the values of the state x(t) and output y(t) remain nonnegative at every time instant t. Also, we say that the system Σ θ is internally stable if the matrix A(θ ) is Hurwitz stable. The parametrized positive model Σ θ arises in various contexts including drug therapy and leader selection [18], as well as dynamical buffer networks [43] and networked epidemics [34], [41] (see Sections IX and VIII for these examples, respectively). In this paper, we consider the following general parameter optimization problem:…”
Section: Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Under these assumptions, for all nonnegative initial condition x(0) and nonnegative input signal u(t) (t ≥ 0), the values of the state x(t) and output y(t) remain nonnegative at every time instant t. Also, we say that the system Σ θ is internally stable if the matrix A(θ ) is Hurwitz stable. The parametrized positive model Σ θ arises in various contexts including drug therapy and leader selection [18], as well as dynamical buffer networks [43] and networked epidemics [34], [41] (see Sections IX and VIII for these examples, respectively). In this paper, we consider the following general parameter optimization problem:…”
Section: Problem Formulationmentioning
confidence: 99%
“…The authors in [14] showed the convexity of the power norm of output signals with respect to the diagonals of the state matrix. The authors in [18] presented an intrinsic convexity property of H 2 and H ∞ state-feedback control problems for positive linear systems. A similar result is obtained in [15] for robust state-feedback stabilization under structured uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…Luenberger pioneered the system theoretic approach to positive systems with his seminal work [8] in the 1980s. Since then various subjects of system theory aspects have been tackled, e.g., realization theory [7], controllability and reachability [9], observability and observer design [10], robust stability [11], [12], positive stabilization [13], [14], fault detection and estimation [15], decentralized and distributed control [16], [17], and, large scale positive systems and scalable control [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to previous works, the proposed approach is not limited to investigating the stability of the network, but aims to automatically design controllers for each of the individual inverters that compose the power system. Starting from the global state space model of the system, local converter controllers are synthesised by solving an optimal H 2 structured control problem [21]. The power of this approach lies in the ability of handling complex control problems, whilst always returning a stable controller with great robustness to system disturbances and parametric uncertainty [22].…”
Section: Introductionmentioning
confidence: 99%